Four-hour acetaminophen concentration estimation after ingested dose based on pharmacokinetic models. (June 2014) - Villeneuve, E.; Gosselin, S.; Whyte, I.
Abstract Introduction. The United Kingdom has recently changed the indications for N-acetylcysteine treatment for acetaminophen intoxication. Any ingestion over 75 mg/kg is now referred to the hospital. A model based on pharmacokinetic parameters was developed to predict 4-h acetaminophen concentration for this and other ingested doses. Methodology. EMBASE and Medline were searched to obtain values for volume of distribution, absorption, and elimination constants and bioavailability for acetaminophen. Four-hour concentrations were calculated for ingestion doses currently recommended for hospital referral in different countries. Calculated plasma concentrations at 4 h for several doses were plotted against the Rumack-Matthew and the United Kingdom treatment lines. Results. Six articles were used for the calculations (4 adult and 2 pediatric). In order to achieve a 4-h acetaminophen concentration of 100 mg/L, doses (mg/kg ± 99.9CI) of 180.5 ± 43.2 for adults and 396.1 ± 115.5 for children were calculated. Discussion. A dose of 75 mg/kg would likely yield a 4-h acetaminophen concentrations well below 100 mg/L. Medical toxicologists and poison information specialists are left without evidence-based guidance for which patients or which ingestion history would now warrant referral to hospital for acetaminophen concentration measurement. Larger toxicokinetic studies in acetaminophen overdose are needed to define ingestion dose for referral to hospital.